Some Observation on Late Babylonian Texts and Rabbinic Literature - Weisberg, David В.
talmudic Aramaic מיזין = Akk. mizru/mazru; מוכתב למלכות and ritta šatāṛu ana; איפזיא and eṭir; הראש שחורי loan translation of ṣalmāt qaqqadi; ארא arru; דנא = dannu; חבית = ḫābû; [פתי = pitnu, pitinu